Right Iliac Fossa Abscess Due to Perforated Appendicitis Presenting with Intraabdominal Mass - Albayrak, Yavuz; Albayrak, Fatih; Dursun, Hakan; Albayrak, Ayse; Uyanık, Muhammet H.; Cerrah, Serkan (Fırat University, 2011)
Acute appendicitis is one of the most common cause of acute abdomen with the peak incidence in early adulthood. We report a case of right iliac fossa abscess resulting from perforated appendicitis. The patient was an 39-year-old woman who had no apparent abdominal signs. She presented with progressive painful swelling of right lower abdomen and the groin for 2 months. Laboratory tests showed a normal white blood cell and anemia. Computed tomography scan demonstrated the presence of abscess at right inguinal site also communicating with the intraabdominal region. At surgery, there was an abscess due to a perforated appendix. Acute appendicitis may have an atypical clinical presentation and should be treated carefully.

Akut apandisit en sık akut karın yapan nedenlerin başında gelir. En sık genç erişkinlerde görülür. Perfore apandisit nedeniyle oluşan sağ iliak fossa apseli bir olguyu sunuyoruz. Otuzdokuz yaşında kadın hastanın 2 aydır süren abdominal belirtilerin bulunmadığı, ilerleyici sağ kasık ağrısı ve ağrılı karın şişliği şikayeti vardı. Laboratuar testlerinde normal beyaz küre sayısı ve anemi vardı. Hastaya yapılan bilgisayarlı tomografide sağ ingüinal bölgede, intraabdominal alanla bağlantılı apse izlendi. Yapılan cerrahi sonrası hastada, perfore apandisite bağlı apse vardı. Akut apandisit, atipik klinik görünümlerle ortaya çıkabilir ve dikkatlice tedavi edilmedir.
İntraabdominal Kitle Olarak Prezente Olan Perfore Apandisite Bağli Sağ İliak Fossa Absesi